Fluidized Bed Membrane Reactor for the Direct Dehydrogenation of Propane: Proof of Concept - Camilla Brencio; Luca Di Felice; Fausto Gallucci (Membranes, 2022)
In this work, the fluidized bed membrane reactor (FBMR) technology for the direct dehydrogenation of propane (PDH) was demonstrated at a laboratory scale. Double-skinned PdAg membranes were used to selectively remove H2 during dehydrogenation tests over PtSnK/Al2O3 catalyst under fluidization. The performance of the fluidized bed membrane reactor was experimentally investigated and compared with the conventional fluidized bed reactor (FBR) by varying the superficial gas velocity over the minimum fluidization velocity under fixed operating conditions (i.e., 500 °C, 2 bar and feed composition of 30vol% C3H8-70vol% N2). The results obtained in this work confirmed the potential for improving the PDH performance using the FBMR system. An increase in the initial propane conversion of c.a. 20% was observed, going from 19.5% in the FBR to almost 25% in the FBMR. The hydrogen recovery factor displayed a decrease from 70% to values below 50%, due to the membrane coking under alkene exposure. Despites this, the hydrogen extraction from the reaction environment shifted the thermodynamic equilibrium of the dehydrogenation reaction and achieved an average increase of 43% in propylene yields.